2018
DOI: 10.1111/aos.13729
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic results of enucleation and/or external beam radiation therapy in 195 retinoblastoma survivors

Abstract: Minor late and potentially treatable effects were seen in patients with implant. Larger sized implants were associated with a higher incidence of ptosis; implant size did not affect subjective outcome with respect to volume or prosthetic motility. Treatment with EBRT had a less favourable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…While the impact of treatment on objective measures, such as overall survival (Yu et al, 2009; Tamboli et al, 2015), subsequent malignancy risk (Chauveinc et al, 2001; Fletcher et al, 2004; Kleinerman et al, 2005; Marees et al, 2008, 2010; Liu et al, 2011; MacCarthy et al, 2013; Fidler et al, 2018), and even ocular cosmesis (Aggarwal et al, 2013; Mourits et al, 2018), has been studied extensively in patients with retinoblastoma, far less data exist on subjective and psychosocial measures, particularly with regard to the impact of enucleation on long-term quality of life. Quantitative studies on quality of life exist with variable results (van Dijk et al, 2007a, 2007b; van Dijk et al, 2009b; Mourits et al, 2018; Zhang et al, 2018). For instance, a study of 65 children and adolescent retinoblastoma survivors demonstrated that survivors reported very good health-related quality of life (van Dijk et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the impact of treatment on objective measures, such as overall survival (Yu et al, 2009; Tamboli et al, 2015), subsequent malignancy risk (Chauveinc et al, 2001; Fletcher et al, 2004; Kleinerman et al, 2005; Marees et al, 2008, 2010; Liu et al, 2011; MacCarthy et al, 2013; Fidler et al, 2018), and even ocular cosmesis (Aggarwal et al, 2013; Mourits et al, 2018), has been studied extensively in patients with retinoblastoma, far less data exist on subjective and psychosocial measures, particularly with regard to the impact of enucleation on long-term quality of life. Quantitative studies on quality of life exist with variable results (van Dijk et al, 2007a, 2007b; van Dijk et al, 2009b; Mourits et al, 2018; Zhang et al, 2018). For instance, a study of 65 children and adolescent retinoblastoma survivors demonstrated that survivors reported very good health-related quality of life (van Dijk et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…After a mean of 42 years since diagnosis, almost a third of study participants (n = 148, 36.9%) still reported that their lives were profoundly affected by loss of one or both eyes due to surgical enucleation, another third (n = 146, 36.4%) reported moderate affect to their lives, and just over a quarter (n = 107; 26.7%) reported low affect. While the impact of treatment on objective measures, such as overall survival (Yu et al, 2009;Tamboli et al, 2015), subsequent malignancy risk (Chauveinc et al, 2001;Fletcher et al, 2004;Kleinerman et al, 2005;Marees et al, 2008Marees et al, , 2010Liu et al, 2011;MacCarthy et al, 2013;Fidler et al, 2018), and even ocular cosmesis (Aggarwal et al, 2013;Mourits et al, 2018), has been studied extensively in patients with retinoblastoma, far less data exist on subjective and psychosocial measures, particularly with regard to the impact of enucleation on long-term quality of life. Quantitative studies on quality of life exist with variable results (van Dijk et al, 2007a(van Dijk et al, , 2007bvan Dijk et al, 2009b;Mourits et al, 2018;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional EBRT of hereditary retinoblastoma with a linear accelerator using the Schipper technique results in severe midface growth inhibition with corresponding cosmetic consequences. Mourits et al could show in 195 retinoblastoma survivors that EBRT resulted in worse cosmetic outcomes compared to enucleation alone [29]. They demonstrated that patients treated with EBRT had significantly more superior sulcus volume deficiencies than those treated with enucleation alone [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mourits et al could show in 195 retinoblastoma survivors that EBRT resulted in worse cosmetic outcomes compared to enucleation alone [29]. They demonstrated that patients treated with EBRT had significantly more superior sulcus volume deficiencies than those treated with enucleation alone [29]. In addition, Mouw et al [18] compared the MRI-based orbital heights and widths of retinoblastoma patients treated with PBT and/or enucleation in a cohort of 12 participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term sequelae are common and often a burden for survivors. Reported side effects include compromised vision aesthetic deficits after surgery or irradiation, platinum-induced ototoxicity and psychosocial late effects [ 28 , 29 , 30 ]. Children with heritable tumor predisposition syndrome carry the risk of developing further second primary malignancies (SPM) related to high mortality [ 31 ].…”
Section: Introductionmentioning
confidence: 99%